(untitled) (University of Khartoum Engineering Journal, 2022)
The aim of this paper is to study the voltage stress and the equipotential mapping for a sample of 33kV porcelain insulator, which is used widely in the Sudanese national grid. The available modeling and analysis package COMSOL multi-physics was used, and a limited number of experiments using the high voltage laboratory facility at University of Khartoum was attempted to compare the simulation and experimental results. The simulation predicts that 30 kV/cm ionization (for air at standard conditions) occurs at about 105 kV, while experimentally ionization started as a visible corona discharge at about 101 kV peak .